Effects of α-tocopherol and citric acid on the oxidative stability of alimentary poultry fats during storage at low temperatures. Issue 5 (4th May 2017) - Pop, Flavia; Mihalescu, Lucia
ABSTRACT: The purpose of this study was to investigate the stability of three alimentary poultry fats (goose, duck, and chicken) by natural antioxidants (α-tocopherol and citric acid). This was targeted to extend their shelf life, and to monitor the quality parameters during refrigerated (+4°C) and frozen storage (–20°C). The addition of natural antioxidants in a proportion of 0.1% has extended the shelf life of goose fat stored at +4°C by 90 days; for goose fat stored at –20°C citric acid has prolonged the shelf life by 150 days, while goose fat with α-tocopherol could be stored for more than 480 days at –20°C without spoilage. Polyunsaturated fatty acids and monounsaturated fatty acids content decreased significantly ( p < 0.05) after 480 days of chilled storage for fat samples with α-tocopherol. The natural antioxidants provided good protection against oxidation of poultry fats, and these can be used to monitor the oxidation of fats and to predict their shelf life stability.